Hans Christian Andersen, prince of storytellers - Greene, Carol (Chicago : Childrens Press, 1991)
A simple biography of the nineteenth-century Danish author known for his fairy tales.
Includes index.
2.6
K-3.
K-3
Keywords: Andersen, H. C., -- 1805-1875 -- Biography -- Juvenile literature; Andersen, H. C., -- 1805-1875.; Andersen, H. C., -- 1805-1875.; Authors, Danish -- 19th century -- Biography -- Juvenile literature; Authors, Danish; Danish authors -- Biography